Paraje resonante (2020)
This project was made in order to reconstruct those moments, moments that have a sentimental charge behind, but they are moments that despite marking us or that perhaps influence who we are or what we will be, we forget very often or even lose details. But with the help of others we can take back those details, such as knowing the name of the person we no longer remember, the color of the jacket we wear that special day or perhaps the people who accompanied us that same day. The three spaces are based on memories of when I was little, each of these memories are linked to different people, people for whom this project was a trigger of emotions and with it, to be able to give back a little of what they have taught me and left on me.